Colonic intussusception in descending colon: An unusual presentation of colon lipoma - Bagherzadeh Saba, Reza (Gastroenterol Hepatol Bed Bench, 2016)
Lipomas of the colon are relatively rare benign soft tissue tumors derived from mature adipocytes of mesenchymatic origin. During colonoscopy, surgery or autopsy they are generally discovered incidentally. Most cases are asymptomatic, with a small tumor size, and do not need any special treatment. However, in the cases with larger in size of tumor some symptoms such as anemia, abdominal pain, constipation, diarrhea, bleeding, or intussusception may be presented. We reported a 47-year-old woman with colonic intussusception in the descending colon caused by colonic lipoma and diagnosed after surgical exploration for obstructive colonic mass.